β-Cyclodextrins Decrease Cholesterol Release and ABC-Associated Transporter Expression in Smooth Muscle Cells and Aortic Endothelial Cells - Coisne, Caroline; Hallier-Vanuxeem, Dorothée; Boucau, Marie-Christine; Hachani, Johan; Tilloy, Sébastien; Bricout, Hervé; Monflier, Eric; Wils, Daniel; Serpelloni, Michel; Parissaux, Xavier; Fenart, Laurence; Gosselet, Fabien (Frontiers in Physiology, 2016)
Atherosclerosis is an inflammatory disease that leads to an aberrant accumulation of cholesterol in vessel walls forming atherosclerotic plaques. During this process, the mechanism regulating complex cellular cholesterol pools defined as the reverse cholesterol transport (RCT) is altered as well as expression and functionality of transporters involved in this process, namely ABCA1, ABCG1 and SR-BI. Macrophages, arterial endothelial and smooth muscle cells (SMCs) have been involved in the atherosclerotic plaque formation. As macrophages are widely described as the major cell type forming the foam cells by accumulating intracellular cholesterol, RCT alterations have been poorly studied at the arterial endothelial cell and SMC levels. Amongst the therapeutics tested to actively counteract cellular cholesterol accumulation, the methylated β-cyclodextrin, KLEPTOSE® CRYSMEβ, has recently shown promising effects of decreasing the atherosclerotic plaque size in atherosclerotic mouse models. Therefore we investigated in vitro the RCT process occurring in SMCs and in arterial endothelial cells (ABAE) as well as the ability of some modified β-CDs with different methylation degree to modify RCT in these cells. To this aim, cells were incubated in the presence of different methylated β-CDs, including KLEPTOSE® CRYSMEβ. Both cell types were shown to express basal levels of ABCA1 and SR-BI whereas ABCG1 was solely found in ABAE. Upon CD treatments, the percentage of membrane-extracted cholesterol correlated to the methylation degree of the CDs independently of the lipid composition of the cell membranes. Decreasing the cellular cholesterol content with CDs led to reduce the expression levels of ABCA1 and ABCG1. In addition, the cholesterol efflux to ApoA-I and HDL particles was significantly decreased suggesting that cells forming the blood vessel wall are able to counteract the CD-induced loss of cholesterol. Taken together, our observations suggest that methylated β-CDs can significantly reduce the cellular cholesterol content of cells forming atherosclerotic lesions and can subsequently modulate the expression of ABC transporters involved in RCT. The use of methylated β-CDs would represent a valuable and efficient tool to interfere with atherosclerosis pathogenesis in patients, nonetheless their mode of action still needs further investigations to be fully understood and finely controlled at the cellular level.